M&A and R&D: Asymmetric effects on acquirers and targets? - Florian Szücs (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
We evaluate the impact of M&A activity on the growth of R&D spending and R&D intensity of 265 acquiring firms and 133 merger targets between 1990 and 2009. We use different matching techniques to construct separate control groups for acquirers and targets and use appropriate difference-in-difference estimation methods to single out the causal effect of mergers on R&D growth and intensity. We find that target firms substantially decrease their R&D efforts after a merger, while the R&D intensity of acquirers drops due to a sharp increase in sales.
Keywords: D22; G34; O3; 330; mergers; R&D growth; R&D intensity; propensity-score matching; difference in difference estimation